Conductive Co3O4/graphene (core/shell) quantum dots as electrode materials for electrochemical pseudocapacitor applications. (1st December 2017) - Shim, Jaeho; Ko, Yohan; Lee, Kyu Seung; Partha, Khanra; Lee, Chil-Hyoung; Yu, Kyoungsik; Koo, Hye Young; Lee, Ki-Tae; Seo, Won-Seon; Son, Dong Ick
Abstract: This work reports on the in-situ chemical synthesis and their properties of the core (active material)/shell (conductive material) type Co3 O4 /graphene quantum dots (QDs). The stable oxygen bridge bonds between the Co3 O4 core and the oxygen-related functional groups on the graphene shells facilitate the efficient charge/discharge performance. The efficient electron transfer process between the Co3 O4 core and the graphene shell lead to an improvement in the electrochemical activity. The specific capacitances of Co3 O4 /graphene QDs electrode, without conductive additives, exhibit high values of 2435 F g −1 at current densities of 1 A g −1 . It breaks through 126% of the initial capacitance after 500 cycles and show above 112% even after 4500 cycles. The excellent performance of the Co3 O4 /G QDs electrode is attributed to the significant improvement of the electrochemical activity, without conductive additives, due to the presence of metal oxide QD covered by graphene shells which leads to the good electrical properties.